Phase change heat transfer during cryosurgery of lung cancer using hyperbolic heat conduction model. (1st May 2017) - Kumar, Ajay; Kumar, Sushil; Katiyar, V.K.; Telles, Shirley
Abstract: The paper reports a numerical study of phase change heat transfer process in lung cancer undergoing cryosurgery. A two dimensional hyperbolic bio-heat model with non-ideal property of tissue, blood perfusion and metabolism is used to analyze the problem. The governing equations are solved by finite difference method based on enthalpy formulation. Effects of relaxation time of heat flux in hyperbolic model on freezing process have been examined. A comparative investigation of two different models (hyperbolic and parabolic bio-heat models) is also presented. Highlights: A 2-D hyperbolic bio-heat model for freezing process in lung cancer is proposed. Non ideal property of tissue, blood perfusion and metabolism are considered. Effects of relaxation time and comparison of two heat conduction models are studied. Relaxation time has significant effect on temperature profile & interfaces position.